Ask More or Ask Less? A Time Management Dilemma during In-Depth Interviews - Kyć, Grzegorz (Pytać więcej czy mniej? Dylemat zarządzania czasem w trakcie wywiadów pogłębionych, 2022)
A dilemma for qualitative research is to achieve adequate data saturation and to reduce the time required for data collection. The aim of the article is to provide an answer to the question: to what extent should an in-depth interview be moderated in order to ensure an adequate level of saturation and time required for the analysis of several topics? The research methods include a literature analysis and an analysis of the author’s dissertation research reports. The article may help to improve the collection of high-quality data during in-depth interviews and to contribute to developing the methodological aspects of qualitative research.
Biblioteka Regionalisty = Regional Journal, 2022, Nr 22, s. 34-44
Keywords: in-depth interview; qualitative research; methodology; saturation; dilemmas; wywiad pogłębiony; badania jakościowe; metodologia; saturacja; dylematy